Commercial law: text, cases, and materials - LS Sealy, RJA Hooley (Oxford university press, 2008)
This book follows a very clear structure, discussing topics covered on commercial law courses not as separate entities, but as part of a coherent whole, enabling students to easily make links between different areas of the law. Fundamental concepts such as ownership, possession, and good faith run through the book, offering common themes connecting each area. The authors supply extensive commentary on key decisions, helping students to focus on the most important areas; also provided are European and American examples, ensuring that students have access to a comparative analysis of commercial law as it operates throughout the world.